APEL pathways: a passport to employment? - Recotillet, Isabelle [Verfasser]; Werquin, Patrick [Verfasser] (My University, 2010)
"It would seem that most policies to promote the use of APEL as a certification method parallel to that offered by formal education and training systems are based on the belief that it is a less costly and shorter method, which is more attractive. Few countries, however, have convincing surveys or observations of the real advantages of APEL for individuals, employers or society as a whole. On the basis of a survey conducted by Dares (Direction de l'animation de la recherche, des études et des statistiques), Drees (Direction de la recherche, de l'évaluation, des études et des statistiques) and Céreq (Centre d'études et de recherches sur les qualifications), this article aims to fill this gap by pinpointing some of the real benefits which applicants gain from embarking on and/or successfully obtaining APEL and the circumstances in which they obtain these benefits." (Autorenreferat, BIBB-Doku)
Keywords: L 2.1.3 Erfahrungslernen; S 2.2.4 Anrechnung, Prüfung & Zertifizierung; L 6.2.3 Evaluation; I 2.2.1 Westeuropa; Erfahrungsorientiertes Lernen; Anerkennung; Zertifizierung; Verfahren; Evaluation; Frankreich